A zonal safety analysis methodology for preliminary aircraft systems and structural design - Chen, Z.; Fielding, John P. (Cambridge University Press, 2018)
Zonal Safety Analysis (ZSA) is a major part of the civil aircraft safety assessment process described in Aerospace Recommended Practice 4761 (ARP4761). It considers safety effects that systems/items installed in the same zone (i.e. a defined area within the aircraft body) may have on each other. Although the ZSA may be conducted at any design stage, it would be most cost-effective to do it during preliminary design, due to the greater opportunity for influence on system and structural designs and architecture. The existing ZSA methodology of ARP4761 was analysed, but it was found to be more suitable for detail design rather than preliminary design. The authors therefore developed a methodology that would be more suitable for preliminary design and named it the Preliminary Zonal Safety Analysis (PZSA). This new methodology was verified by means of the use of a case study, based on the NASA N3-X project. Several lessons were learnt from the case study, leading to refinement of the proposed method. These lessons included focusing on the positional layout of major components for the zonal safety inspection, and using the Functional Hazard Analysis (FHA)/Fault Tree Analysis (FTA) to identify system external failure modes. The resulting PZSA needs further refinement, but should prove to be a useful design tool for the preliminary design process.
Keywords: Zone partition; Design and installation guideline; External failure mode; Inspection; Risk assessment; Modification